Blinkered bioethics - Benatar, S. R. (Journal of medical ethics, 2004)
The blinkered debate on organ donation neglects the widening gap between the developed and developing worlds The current debate about organ donation and the associated advocacy for selling kidneys, while laudable for its concern about increasing the ability to save the lives of some people with chronic renal failure, is characterised by four features that locate the reasoning process within a narrow and inadequate framework. Firstly, the focus on saving lives is myopic, with the lives of the most privileged in the world receiving most attention. Secondly, the debate is firmly set within a value system in which market values dominate. Thirdly, health is considered from a highly individualistic perspective with little understanding of the importance of social solidarity in health. Finally, a constricted moral vocabulary is used to discuss the ethics of organ sales. Many articles making pleas for more organs begin by describing the number of people waiting for donated organs, the number of donors who could give organs but are not doing so, and how many lives could be saved if more organs could be made available. Great concern is expressed about a few thousand …